USING KWL (KNOW-WANT TO KNOW-LEARNED) STRATEGY IN IMPROVING STUDENTS’ READING COMPREHENSION - Nirwan Nirwan (Universitas Syiah Kuala, 2020)
This experimental study aimed to investigate the effects of the use of KWL (Know-Want to Know-Learned) strategy in teaching reading comprehension. The population of this study was 120 students, while the samples consisted of 60 English department students enrolled in the second semester. The sample was divided into two groups; the experimental group (EG) and the control group (CG). The sample was chosen through random sampling technique. The instruments used in collecting the data were test and questionnaire. The data were analyzed through non-parametric statistical in SPSS 20. The result of Wilcoxon test was 0.00 lower than 5%. The findings reveal that there was significant difference in reading comprehension achievement between EG and CG. The mean score of the post-test for the EG was 9.92, while the mean score for post-test of CG was 7.91. Hence, it can be concluded that the alternative hypothesis was accepted and the null hypothesis was rejected. Consequently, the use of KWL strategy has proven a significance improvement in the students’ reading comprehension. Some implications are derived for both students and teachers.